ANALYZING OCCUPATIONAL HEALTH AND SAFETY TEACHING PRACTICES IN TECHNICAL UNIVERSITIES: A CONVERGENT MIXED METHODS STUDY (Ideal Journal of Multidisciplinary Research, 2026)
Occupational health and safety (OHS) education in engineering programs faces persistent challenges in developing students' risk-based decision-making competencies. Despite established curricula, gaps remain between what is taught and what students can actually apply in professional contexts.
Keywords: Occupational health and safety education; engineering education; risk-based decision making; competency-based assessment; mixed methods research; pedagogical innovation.